2015
DOI: 10.1111/ppe.12197
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain Trend and Population Attributable Risks of Adverse Fetal Growth Outcomes in Ohio

Abstract: Background The trend of gestational weight gain (GWG) in relation to the Institute of Medicine (IOM) guidelines and population attributable risks (PARs) of GWG on fetal growth outcomes remain unclear. Methods We analyzed Ohio birth certificates from 2006 to 2012 to examine GWG trend by prepregnancy body mass index, to calculate the risk of small- and large-for-gestational-age (SGA and LGA), and macrosomia (birthweight >4000 g or >4500 g) infants, and to estimate the PARs of GWG below or above the guidelines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Increasing BMI is often considered a risk factor for the majority of obstetric outcomes in a more dose–response fashion across the BMI spectrum (e.g. post‐partum haemorrhage, large for gestational age infants), while we found increased odds of regional anaesthesia complications only in primiparous women with morbid obesity and super obesity, and in multiparous women with super obesity. It is worth noting that non‐monotonic relationship observed between BMI and adverse regional anaesthesia outcomes is also observed with some other outcomes (e.g.…”
Section: Commentmentioning
confidence: 48%
“…Increasing BMI is often considered a risk factor for the majority of obstetric outcomes in a more dose–response fashion across the BMI spectrum (e.g. post‐partum haemorrhage, large for gestational age infants), while we found increased odds of regional anaesthesia complications only in primiparous women with morbid obesity and super obesity, and in multiparous women with super obesity. It is worth noting that non‐monotonic relationship observed between BMI and adverse regional anaesthesia outcomes is also observed with some other outcomes (e.g.…”
Section: Commentmentioning
confidence: 48%
“…11,12 Current trends for weight gain among women of reproductive age are alarming. 13,14 Precise estimates of GDM prevalence are not clear. A recent meta-analysis reported that the prevalence of GDM in Europe is 5.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Only three published studies 11‐13 have examined GWG trends in the United States. Harris et al (2014) 12 found average GWG fell by 0.24 lbs/year and inadequate GWG increased by 0.4%/year in Maine from 2000 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al (2014) 12 found average GWG fell by 0.24 lbs/year and inadequate GWG increased by 0.4%/year in Maine from 2000 to 2010. Chen et al (2015) 11 concluded a slight change in Ohio in the percentages of GWG below, within or above the IOM guidelines without discussing directions 11 . Johnson et al (2015) 13 used the 14‐state data from the Pregnancy Risk Assessment Monitoring System (PRAMS) and concluded that average GWG and the percentage with GWG below IOM recommendations stayed about the same over time, but there was a biennial 1.0% GWG decrease within and 0.8% GWG increase above IOM recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation